Detection of a High Ratio of Soluble to Membrane‐Bound LOX‐1 in Aspirated Coronary Thrombi From Patients With ST‐Segment–Elevation Myocardial Infarction. Issue 2 (21st January 2020) - Lee, An‐Sheng; Wang, Yu‐Chen; Chang, Shih‐Sheng; Lo, Ping‐Hang; Chang, Chia‐Ming; Lu, Jonathan; Burns, Alan R.; Chen, Chu‐Huang; Kakino, Akemi; Sawamura, Tatsuya; Chang, Kuan‐Cheng
Abstract : Background: The circulating level of soluble lectin‐like oxidized low‐density lipoprotein receptor‐1 (sLOX‐1) is a valuable biomarker of acute myocardial infarction (AMI). The most electronegative low‐density lipoprotein, L5, signals through LOX‐1 to trigger atherogenesis. We examined the characteristics of LOX‐1 and the role of L5 in aspirated coronary thrombi of AMI patients. Methods and Results: Intracoronary thrombi were aspirated by performing interventional thrombosuction in patients with ST‐segment–elevation myocardial infarction (STEMI; n=32) or non–ST‐segment–elevation myocardial infarction (n=12). LOX‐1 level and the ratio of sLOX‐1 to membrane‐bound LOX‐1 were higher in thrombi of STEMI patients than in those of non–ST‐segment–elevation myocardial infarction patients. In all aspirated thrombi, LOX‐1 colocalized with apoB100. When we explored the role of L5 in AMI, deconvolution microscopy showed that particles of L5 but not L1 (the least electronegative low‐density lipoprotein) quickly formed aggregates prone to retention in thrombi. Treating human monocytic THP‐1 cells with L5 or L1 showed that L5 induced cellular adhesion and promoted the differentiation of monocytes into macrophages in a dose‐dependent manner. In a second cohort of AMI patients, the L5 percentage and plasma concentration of sLOX‐1 were higher in STEMI patients (n=33) than in non–ST‐segment–elevation myocardial infarction patients (n=25), and sLOX‐1 level positively correlated with L5 level in AMI patients. Conclusions: The level of LOX‐1 and the ratio of sLOX‐1 to membrane‐bound LOX‐1 in aspirated thrombi, as well as the circulating level of sLOX‐1 were higher in STEMI patients than in non–ST‐segment–elevation myocardial infarction patients. L5 may play a role in releasing a high level of sLOX‐1 into the circulation of STEMI patients.